Acidithiobacillus caldus sulfur oxidation model based on transcriptome analysis between the wild type and sulfur oxygenase reductase defective mutant. - Linxu Chen (Public Library of Science (PLoS), 2012)
Background Acidithiobacillus caldus (A. caldus) is widely used in bio-leaching. It gains energy and electrons from oxidation of elemental sulfur and reduced inorganic sulfur compounds (RISCs) for carbon dioxide fixation and growth. Genomic analyses suggest that its sulfur oxidation system involves a truncated sulfur oxidation (Sox) system (omitting SoxCD), non-Sox sulfur oxidation system similar to the sulfur oxidation in A. ferrooxidans, and sulfur oxygenase reductase (SOR). The complexity of the sulfur oxidation system of A. caldus generates a big obstacle on the research of its sulfur oxidation mechanism. However, the development of genetic manipulation method for A. caldus in recent years provides powerful tools for constructing genetic mutants to study the sulfur oxidation system. Results An A. caldus mutant lacking the sulfur oxygenase reductase gene (sor) was created and its growth abilities were measured in media using elemental sulfur (S(0)) and tetrathionate (K(2)S(4)O(6)) as the substrates, respectively. Then, comparative transcriptome analysis (microarrays and real-time quantitative PCR) of the wild type and the Δsor mutant in S(0) and K(2)S(4)O(6) media were employed to detect the differentially expressed genes involved in sulfur oxidation. SOR was concluded to oxidize the cytoplasmic elemental sulfur, but could not couple the sulfur oxidation with the electron transfer chain or substrate-level phosphorylation. Other elemental sulfur oxidation pathways including sulfur diooxygenase (SDO) and heterodisulfide reductase (HDR), the truncated Sox pathway, and the S(4)I pathway for hydrolysis of tetrathionate and oxidation of thiosulfate in A. caldus are proposed according to expression patterns of sulfur oxidation genes and growth abilities of the wild type and the mutant in different substrates media. Conclusion An integrated sulfur oxidation model with various sulfur oxidation pathways of A. caldus is proposed and the features of this model are summarized.